Interpolation of local potential parameters in allocating village fund formulation as an effort to development of local-based tourism - Fazal Akmal Musyarri (Indonesian Tourism Journal, 2024)
The development of Indonesia tourism today has experienced a significant increase. This is inseparable from the role of great tourism potential in Indonesia. The village tourism sector can be developed through cultural wealth, education, and ecotourism. However, issues have arisen in the efforts to manage tourism, particularly in rural areas, due to the suboptimal role of the government in managing tourism potential Conversely, in order to optimize village authority, Villages Law provides financial assistance in the form of Village Funds, which come from a basic allocation fund of 90% that is the same for all villages, plus a formulation fund of 10% which represents the difference in the amount of village funds received between villages. The formulation fund is adjusted to the Number of Population (25%), Number of Poor (35%), Village Area (10%) and geographical difficulty (30%). Unfortunately, the division of parameters is consumptive and not productive, in the sense that there is no division of parameters for the local potential of villages that differ from one village to another. Therefore, the author initiated the idea of adding parameters to the village's local potential in the distribution of village fund formulation funds. The research method used in this scientific work is normative juridical. The addition of local potential parameters in the distribution of village fund formulation funds includes the potential of the village tourism sector. With the implementation of this idea, it is expected to optimize tourism management efforts and increase the potential of the tourism sector in Indonesia.